Tarski's world [Jon Barwise & John Etchemendy]. - Barwise, Jon.; Etchemendy, John, 1952- (Stanford, CA : CSLI Publications, 1993)
A computer-based introduction to first-order logic, intended as a supplement to a logic text.
Title from disk label.
Issued also for NeXT and Macintosh computers.
System requirements: IBM-compatible PC; DOS; Microsoft Windows 3.0 or greater; mouse recommended.
Keywords: First-order logic -- Software